VD_FINDINFO Décision / 2013 / 937 vom 28. März 2003 - VD Tribunal cantonal (2003)
LIBÉRATION CONDITIONNELLE, DÉTENTIONINCARCÉRATION, MESURE PROVISIONNELLE | 89 al. 4 CP, 95 al. 3 CP, 95 al. 5 CP, 26 LEP, 38 al. 1 LEP, 364 CPP (CH), 62 al. 1 CPP (CH)